THE CONTACT PROBLEM STUDY OF THE SELF DUMPING TRUCK DRIVING AXLE HOUSING USING RESPONSE SURFACE METHOD - SUN YongGang (Jixie qiangdu)
The finite element method is applied to the numerical simulation test of a dumping truck drive axle housing contact region,in order to reflect the non-linear mechanical property the CCD method is adopted to guide the test,the RSM is fitted according to the result of the test. the variance analysis of the RSM show that the RSM can describe clearly and significantly the nonlinear problem of the self dumping truck driving axle housing,the guiding suggestions are put forward based on the analysis of the RSM.